The KEAP1/NRF2 Signaling Pathway in Keratinization - Yosuke Ishitsuka; Tatsuya Ogawa; Dennis Roop (Antioxidants, 2020)
Keratinization is a tissue adaptation, but aberrant keratinization is associated with skin disorders such as ichthyoses, atopic dermatitis, psoriasis, and acne. The disease phenotype stems from the interaction between genes and the environment; therefore, an understanding of the adaptation machinery may lead to a new appreciation of pathomechanisms. The KEAP1/NRF2 signaling pathway mediates the environmental responses of squamous epithelial tissue. The unpredicted outcome of the Keap1-null mutation in mice allowed us to revisit the basic principle of the biological process of keratinization: sulfur metabolism establishes unparalleled cytoprotection in the body wall of terrestrial mammals. We summarize the recent understanding of the KEAP1/NRF2 signaling pathway, which is a thiol-based sensor-effector apparatus, with particular focuses on epidermal differentiation in the context of the gene-environment interaction, the structure/function principles involved in KEAP1/NRF2 signaling, lessons from mouse models, and their pathological implications. This synthesis may provide insights into keratinization, which provides physical insulation and constitutes an essential innate integumentary defense system.